DEONTOLOGICAL COMPETENCE OF FUTURE SPECIALISTS IN THE SOCIO-ECONOMIC SPHERE IN THE PROCESS OF PROFESSIONAL TRAINING - Tiulpa, T. (SWorld-Ger Conference proceedings, 2024)
Abstract. The article reveals the relevance of the problem of professional training of future specialists in the socionomic sphere on deontological grounds. The professional activity of specialists in socio-economic professions is justified in the context